Application of Lean Concepts in Shipbuilding On The Example of Çimtas Module & Shipyard - Piotr Walentynowicz; Pamela Omiotek (Communications of International Proceedings, 2023)
The article presents considerations on the theory and practice of the current state of application of Lean Management in the shipbuilding industry, with particular emphasis on the case of Çimtas Module & Shipyard. This case proves that in shipbuilding the use of Lean Management can bring many benefits to the company. Although the theoretical foundations of the application of Lean Management in the shipbuilding industry are quite well developed and presented in the literature, in practice in shipbuilding Lean Management is not used as often as it deserves. Especially in Europe and in the shipyard sector. It is much better in the countries of the Far East, especially in Japan, but there is still a lot to be done in this area. As a result of the conducted research, mainly using the method of literature studies, it was also identified that the introduction of Lean Management to the company creates a very good basis for the implementation of digital solutions in the area of Industry 4.0, which have recently become more and more popular in the shipbuilding industry.
Keywords: Lean Management; shipbuilding; Lean Shipbuilding; Lean Shipyard.